THE LIMBIC-HYPOTHALAMIC-PITUITARY-ADRENAL AXIS AND THE DEVELOPMENT OF ALCOHOL USE DISORDERS IN YOUTH - Schepis, Ty S. (2011)
OBJECTIVE: As the initiation and acceleration of alcohol use commonly occurs during adolescence, the etiological basis for this phenomenon is of critical importance. Using the diathesis-stress model as a framework, this review will evaluate the emerging evidence implicating the limbic-hypothalamic-pituitary-adrenal (LHPA) axis in the development of alcohol use disorder (AUD). METHOD: Searches were conducted of the PubMed/Medline, PsycInfo, PsycBooks, Cochrane and ISI Web of Science databases, using a specified set of search terms. RESULTS: Genetic liabilities, antenatal stress/anxiety or exposure to addictive substances, exposure to maltreatment or other traumatic events in childhood and psychiatric illness in childhood/adolescence can all increase the risk, or diathesis, for AUD. Greater LHPA dysfunction may serve as a marker for higher diathesis levels in youth. When exposed to stressors in adolescence, high-risk youth (or those with greater LHPA dysfunction) may use alcohol and/or other substances to cope with stressors and, in turn, become more vulnerable to AUD. CONCLUSION: Evidence suggests that LHPA dysfunction and stress play an important role in the development of AUD. Genetic liabilities, antenatal insults, maltreatment and psychiatric illness appear to increase LHPA dysfunction, raising risk for AUD. Further research is needed to clarify the complex interplay among adverse developmental experiences, LHPA dysfunction and the development of AUD in adolescents.